Thrombosis of a parametrial vein with subsequent recanalization-A case report - Nina Koehler; René Hornung (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Background: Thrombosis of parametrial veins are rarely diagnosed by transvaginal sonography. The clinical importance of parametrial vein thrombosis is not known. We present the first fully documented case of pelvic varicosities with non-occlusive thrombosis resulting in subsequent development of pelvic pain that alleviated with the resolution of the thrombus. Case report: We present a perimenopausal woman that underwent transvaginal sonography for routine check-up. The patient sustained a thrombosis in the parametrial vein that some days later caused minor pain and dissolved spontaneously within three months. Discussion and conclusion: Transvaginal sonography should also focus on the venous pelvic system and look for thrombosis. Thrombosis of dilated pelvic veins may play a role in the pathogenesis of the pelvic congestion syndrome in a sense that pelvic vein varicosities that develop a thrombus evolve from an asymptomatic anatomic description of dilated veins to a pelvic pain disorder requiring treatment.